Handling Health Care Waste Management and gender differences in the Madinah Primary Healthcare Centers, Kingdom of Saudi Arabia - Talaat H. Habeeb; Shaharuddin Ahmad (Faculty of Social Sciences and Humanities, UKM,Bangi, 2015)
Health care waste management (HCWM) is a major challenge in developing countries. Poor HCWM will exacerbate the risk of infection. HCW segregation is considered the most important step of health care waste management (HCWM). This article attempts to analyze and evaluate gender differences in their perception of HCW segregation at the Madinah primary health care centers (PHCC) in the Kingdom of Saudi Arabia (K.S.A.). Questionnaire surveys were conducted to gather primary data from 925 respondents (230 females and 225 males) at various PHCCs in Madinah. Data were then analyzed using the SPSS and PLS-smart 2.0. In general, female respondents had higher qualifications and income, and longer working experience than males. About 80% of the departments managed by females had the correct type of container compared to the males’ 42%. The study also found that the waste segregation at the PHCCs was poor as it was not achieved at 34.1% of all the departments. Similarly, the results of the hypothesis tests showed that waste segregation in PHCC did not have a direct relationship with HCWM (0.0001; t = 0. 0015) just as there were no direct relationships between waste segregation of males and females with HCWM ( 0.0565; t=1.3669).